Construction of network ecological civilization based on the anti-terrorism of colleges and universities - You-deng CHEN (网络与信息安全学报)
Firstly,the basic connotation,significance and potential crisis of the network ecological civilization were introduced.Secondly,the basic situation of the current network terrorism and the challenge to the human civilization and security were analyzed,and the information dissemination was the foundation and that the key point of building the network ecological civilization was put forward.Finally,from the construction of the network discourse system,the construction of the network culture system,the construction of the network ethics system,the planning suggestions were put forward to explore and perfect the construction of the anti-terrorism path of the university network in our country.